2017
DOI: 10.5430/ijfr.v9n1p50
|View full text |Cite
|
Sign up to set email alerts
|

Does the January Effect Still Exists?

Abstract: The issue of the January Effect has attracted a lot of interest by both practitioners and researchers. The idea that stock returns in January are statistically bigger than in other months was first presented several decades ago. This study analyzes the issue of the January effect in a systematic and global way of studying the performance of 106 indexes in 86 countries and jurisdictions. It was observed that while this effect can still be appreciated in some markets it would appear that it is decreasing globall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…Our results are consistent with the existing literature. The fact that a complete history of the various markets was used adds weight to the work of Marquering et al (2006), Perez (2018) and Rossi & Gunardi (2018), amongst others, who in the main highlighted the disappearance of anomalies over time. Or in other words, that markets evolve to become more efficient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are consistent with the existing literature. The fact that a complete history of the various markets was used adds weight to the work of Marquering et al (2006), Perez (2018) and Rossi & Gunardi (2018), amongst others, who in the main highlighted the disappearance of anomalies over time. Or in other words, that markets evolve to become more efficient.…”
Section: Resultsmentioning
confidence: 99%
“…Post the initial wave of the confirmation of the January effect, more evidence from recent studies is mixed. Suggesting that the January effect has since disappeared in advanced markets (see Marquering et al (2006) and Perez (2018)). For example, Floros (2008) found no evidence of the January effect in the Greek stock market, Rossi & Gunardi (2018) found no evidence of the January effect in advanced markets between 2001 and 2010, and Giovanis (2009) found no evidence of the January effect in 36 out of 55 stock markets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…On the day of the week anoma-ly, there is a difference for each daily return for one week. Perez (2018) has researched and analyzed the existence and issue of the January Effect in a systematic and around the world, studying the performance of 106 indexes in 86 countries and jurisdictions. It is found that some studies detect the January Effect, and some do not.…”
Section: Introductionmentioning
confidence: 99%